Learning Perceptive Mental Processes in Angkola Language - Pulungan, Husniah Ramadhani; Chalimah, Chalimah; Daulay, Muhammad Roihan; Masuwd, Mowafg Abrahem; Kristiawan, Muhammad (Anglophile Journal, 2022)
This article aims to reveal the learning of patterns and cultural influences of perceptive mental processes in Angkola language with a Systemic Functional Linguistics (SFL) approach. This is because learning research tends to offer research related to language learning models and language learning media from various perspectives. Meanwhile, the content of the learning is still limited to be analyzed in certain grammar. This research offers perceptive mental process learning based on one of the regional languages in Indonesia, namely Angkola language which needs to be raised considering that this language still includes native speakers. Thus, the Angkola language must be included in the list of documentation of languages and oral traditions that should be preserved in order to maintain the wealth of the archipelago. The method used is descriptive qualitative with transitivity analysis. The results of the analysis show that the Angkola community in expressing perceptive mental processes produces two patterns, one sequential pattern and one non-sequential pattern. However, for non-sequential patterns, after the process is not followed by sensing but is followed by a phenomenon then sensing afterwards. The uniqueness and symptoms of this strangeness are found in the study of perceptive mental processes in the Angkola language. Therefore, according to the presentation of the analysis, it can be proven the consistency, prevalence and acceptance of this pattern in transitivity in the Angkola language. Keywords: Angkola Language, Mental Process Language, Systemic Functional Linguistics